The Graphs of Quadratic Equations A quadratic equation is an equation that has a x 2 value. All of these are quadratics: y = x 2 y = x y = x 2 + x – 4 y = x 2 + 2x – 3 Sunday, 20 December 2015 So quadratic means that there must be a x 2 in what ever y equals
If you were asked to draw the graph of y = x 2 + 2, follow these steps 1) Draw a chart putting in the x values from – 4 to +4 x The exam writer will probably do this for you
If you were asked to draw the graph of y = x 2 + 2, follow these steps 2) Calculate x 2 and put these values into the table. Notice that all of these are positive x x2x The values are always positive because a minus time a minus is a plus -3 X –3 = 9 etc.
If you were asked to draw the graph of y = x 2 + 2, follow these steps 3) Add the 2 onto the x 2 and put these values into the table. x x2x x
If you were asked to draw the graph of y = x 2 + 2, follow these steps 4) You have done all that the equation asks so you will have the y value. x x2x x y All you need to do now is to plot the x number against the y number.
x x2x x y
If you were asked to draw the graph of y = x 2 + x – 4, follow these steps 1) Draw a chart putting in the x values from – 4 to +4 x The exam writer will probably do this for you
If you were asked to draw the graph of y = x 2 +x – 4, follow these steps 2) Calculate x 2 and put these values into the table. Notice that all of these are positive x x2x The values are always positive because a minus time a minus is a plus -3 X –3 = 9 etc.
If you were asked to draw the graph of y = x 2 + x – 4, follow these steps 3) Add the x onto the x 2 and put these values into the table. x x2x x 2 +x
If you were asked to draw the graph of y = x 2 + x – 4, follow these steps 3) Subtract 4 from these values to obtain x 2 + x – 4. x x2x x 2 +x x 2 + x –
If you were asked to draw the graph of y = x 2 + x – 4, follow these steps 3)You have done all the equation asks so you must have the y value. x x2x x 2 +x x 2 + x – y All you need to do now is to plot the x number against the y number
x x2x x 2 +x x 2 + x – y